2021
DOI: 10.3390/ani11030857
|View full text |Cite
|
Sign up to set email alerts
|

From the Andes to the Apennines: Rise and Fall of a Free-Ranging Population of Feral Llamas

Abstract: Since 2016, a feral population of llama Lama glama has been present in Central Italy after escaping from a zoological garden and starting to reproduce. We updated demographic status and distribution of this population and investigated societal perception towards the llama presence and management in the area through a standard questionnaire. Field data were collected through direct (transects traveled by car and on foot) and indirect (newspapers, social networks and online platforms) research. The feral populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Moreover, the Spanish case suggests that beaver removal even following illegal releases is complicated and may be unsuccessful, resulting in wasted resource (Mori et al 2021b;Calderón et al 2022;González-Calderón et al 2023). Accordingly, in Southern Europe, apart from some extreme animal-right groups, a general consensus and awareness of the impacts of biological invasions seems to occur in the general public (e.g., in the case of grey squirrels Sciurus carolinensis, Siberian chipmunks Eutamias sibiricus and free-ranging llamas Lama glama: La Morgia et al 2017;Lioy et al 2019;Cerri et al 2020;Gargioni et al 2021). Similarly, charismatic fauna e.g., domestic rabbits Oryctolagus cuniculus domesticus (Sogliani et al 2021), brown bear Ursus arctos (Glikman et al 2019), loggerhead turtles Caretta caretta (Jones et al 2011), and beavers (this work) mostly elicit positive attitudes in the general public.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the Spanish case suggests that beaver removal even following illegal releases is complicated and may be unsuccessful, resulting in wasted resource (Mori et al 2021b;Calderón et al 2022;González-Calderón et al 2023). Accordingly, in Southern Europe, apart from some extreme animal-right groups, a general consensus and awareness of the impacts of biological invasions seems to occur in the general public (e.g., in the case of grey squirrels Sciurus carolinensis, Siberian chipmunks Eutamias sibiricus and free-ranging llamas Lama glama: La Morgia et al 2017;Lioy et al 2019;Cerri et al 2020;Gargioni et al 2021). Similarly, charismatic fauna e.g., domestic rabbits Oryctolagus cuniculus domesticus (Sogliani et al 2021), brown bear Ursus arctos (Glikman et al 2019), loggerhead turtles Caretta caretta (Jones et al 2011), and beavers (this work) mostly elicit positive attitudes in the general public.…”
Section: Discussionmentioning
confidence: 99%
“…Our study area was defined by the region in which the beavers have been identified, and residents in this area may have had direct experience with the species. The participants were convenience sampled as this is an early-stage, exploratory study to gain an indicative insight into the attitudes of people who live in the local area (Muboko et al 2016;Gargioni et al 2021). Whilst this means numbers cannot be directly inferred to represent the prevalence of opinions in wider populations, the study places emphasis on exploring levels of support for reintroduction among this group in response to participant background variables.…”
Section: Participants and Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual rate of first records worldwide has increased during the last 200 years, with 37% of all first records reported in the last four decades 4 , when the number of invasive alien species has dramatically increased particularly in Europe, with extensive impacts on the native biodiversity 5 . Escapes from captivity are one of the main pathways of alien species introduction 6 , often resulting in self-sustaining populations 7 10 . Since 2014, the European Union Regulation 1143/2014 has been adopted to prevent and manage the introduction and spread of invasive taxa, based on a list of alien species of Union concern, identified through detailed risk assessments 11 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, various studies have developed psychometric scales to measure attitudes towards one or more IAS in specific circumstances, often within management or eradication programs (e.g., Siberian chipmunk Eutamias sibiricus in Northern Italy: Cerri et al 2020; feral llamas Llama glama in Central Italy: Gargioni et al 2021; see Kapitza et al 2019 for a review). However, fewer tried to develop broadlyapplicable attitudinal scales, to measure overall beliefs about IAS and their management, similarly to what has been done for other psychological constructs (e.g., wildlife value orientations, Manfredo et al 2009).…”
Section: Introductionmentioning
confidence: 99%